Assessment Perkembangan Seni Pada Anak Usia Dini - Mufidah, Khirzatul; Laiqotus Salwa; Siti Isnaini; Fu'ad Arif Noor (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2024)
This research was carried out at RA Ma'hadul Ulum with the aim of evaluating teacher performance in developing children's artistic potential and identifying their needs, as well as planning appropriate strategies to stimulate artistic growth according to the stages of early childhood development. This research involved 13 students from the Play group consisting of 10 girls and 3 boys. Data collection was carried out through observation, children's work such as coloring, pasting, cutting and collage, as well as demonstrations of children's skills such as dancing and gymnastics. The methods used include checklists, narratives and portfolios. The assessment results use descriptions in the form of semester reports and weekly checklists. The educational evaluation and assessment standards at RA Ma'hadul Ulum are considered very good, in accordance with early childhood education guidelines. However, daily recording is not always done every day according to established procedures, but teachers still record weekly. Overall, children's artistic development is in line with the expectations that have been set.